Are climate change adaptation and mitigation options eco-efficient? - Jarvis, Andy; Ramírez Villegas, Julián Armando; Tapasco, Jeimar; Navarro Racines, Carlos Eduardo; Peterson CA; Zapata Caldas, E.; Fisher MJ (International Center for Tropical Agriculture, 2013)
This chapter provides an overview of predicted global climate change, placing special emphasis on the implications for agriculture. The power of modelling for understanding both impacts on productivity and adaptation options is demonstrated. The models on agricultural production for 50 crops predict significant impacts, with both winners and losers. The resultant need for systems reconstruction in highly vulnerable areas demonstrates a possible entry point for eco-efficient agriculture, in parallel with demands for adaptation measures that are climate smart and deliver on mitigation co-benefits. The chapter then focuses on Colombia and provides an end-to-end analysis of projected climatic changes for 2050, the impacts this may have on agriculture, and mitigation and adaptation options in the country s rice sector. Priority options include managing the methane emissions of flooded rice, eliminating crop residue burning, irrigation, genetic modification for heat tolerance, and increasing efficiency of nitrogen fertilizer application. The relevance of eco-efficient agriculture in adapting to and mitigating climate change is discussed, with special emphasis on synergies between eco-efficiency and climate change adaptation or mitigation.